2016
DOI: 10.1111/ans.13738
|View full text |Cite
|
Sign up to set email alerts
|

Is resection of pancreatic adenocarcinoma with synchronous hepatic metastasis justified? A review of current literature

Abstract: Multi-institutional prospective studies are required to fully delineate the potential therapeutic utility and operative indications of liver metastasectomy in the setting of modern interdisciplinary management of PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
0
21
0
3
Order By: Relevance
“…The feasibility and safety of combined pancreatectomies and liver resections has been already demonstrated (95). Actually most patients resected for M1 liver PDAC reported in the literature underwent wedge/atypical only liver resections (96)(97)(98).…”
Section: Resection For M1 Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility and safety of combined pancreatectomies and liver resections has been already demonstrated (95). Actually most patients resected for M1 liver PDAC reported in the literature underwent wedge/atypical only liver resections (96)(97)(98).…”
Section: Resection For M1 Pdacmentioning
confidence: 99%
“…Interestingly, a recent multicentric study has shown that the overall survival is significantly higher in patients with oligometastatic M1 PDAC of the head who underwent resection, compared with bypass, while for M1 PDAC of the body and tail no differences were observed (102). Recent reviews of the literature have shown that resection for M1 liver PDAC might have a survival benefit in carefully selected patients, particularly with metachronous metastases (96,98).…”
Section: Resection For M1 Pdacmentioning
confidence: 99%
“…Approximately 49.5% of patients present distant metastases at the time of a pancreatic cancer diagnosis. The median OS of metastatic pancreatic ductal adenocarcinoma (PDAC) is less than 12 months if treated with chemotherapy [1].…”
Section: Introductionmentioning
confidence: 99%
“…The primary cause of death for patients with pancreatic adenocarcinoma is metastatic disease rather than local recurrence. Antoniou et al have shown that pancreatic metastasectomy can now be undertaken safely but also that hepatic resection is not enough to ensure cure. The results of the ACCORD 11 trial confirm that FOLFIRINOX is active against pancreatic adenocarcinoma and that discussion should commence around criteria to select patients in whom hepatic resection or ablation might be offered.…”
mentioning
confidence: 99%
“…The results of the ACCORD 11 trial confirm that FOLFIRINOX is active against pancreatic adenocarcinoma and that discussion should commence around criteria to select patients in whom hepatic resection or ablation might be offered. As Antoniou et al point out in their final paragraph, approaches historically based on solitary or unilobar disease have met success for metastatic colorectal cancer, and neuroendocrine, non‐colorectal, and non‐neuroendocrine tumours. More recently, biological selection based on a favourable response to systemic therapy has been employed for these tumour types either by standard cross‐sectional or functional imaging.…”
mentioning
confidence: 99%